2019
DOI: 10.1371/journal.pone.0217253
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors for postoperative meningitis after microsurgery for vestibular schwannoma

Abstract: Objective Meningitis after microsurgery for vestibular schwannoma (VS) is a severe complication that results in high morbidity. However, few studies have focused on meningitis after VS surgery. The purpose of this study was to identify the risk factors for meningitis after VS surgery. Methods We performed a retrospective analysis of all VS patients who underwent microsurgery and survived for at least 7 days after surgery, between 1 June 2015 and 30 November 2018 at West… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…We found that IBL ≥400 mL was an independent risk factor for the POM. This observation was in-concurrence with previous studies reporting the correlation between IBL and POM ( 33 , 34 ). The large amount of IBL may compromise the patient’s immune system and adversely influence the physiology of local brain tissue.…”
Section: Discussionsupporting
confidence: 93%
“…We found that IBL ≥400 mL was an independent risk factor for the POM. This observation was in-concurrence with previous studies reporting the correlation between IBL and POM ( 33 , 34 ). The large amount of IBL may compromise the patient’s immune system and adversely influence the physiology of local brain tissue.…”
Section: Discussionsupporting
confidence: 93%
“…The second feature was that no microorganism was cultured in the CSF specimens. Of course, we could not verify that the negative culture results always corresponded to aseptic meningitis because the isolation rate of the CSF culture was approximately 33% and perioperative antibiotics influenced the culture results [ 15 , 30 ]. The third one was that the time to infection was longer than 8 days (range, 8–38) after the operation in half of the infected patients, which was longer than that of postcraniotomy meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative meningitis after craniotomy is a common complication of neurosurgery and affects the prognosis of surgical patients. Some malignant tumors and tumors of the ventricular system are prone to cause postoperative intracranial infection [14,15]. Bacterial meningitis is more common in infection [16].…”
Section: Selection Of Antibiotics During Lcdmentioning
confidence: 99%